ANALISIS PENDAPATAN DAN PROSPEK PENGEMBANGAN USAHA IKAN SALAI PATIN DI DESA SIDORAHAYUKECAMATAN BELITANG KABUPATEN OKU TIMUR - ANGGI Fatmayati (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2023)
Catfish is a preserved product by utilizing a combination of drying treatment and chemical compounds from the combustion of natural fuels. Based on this, the results of the study show that the income of the salai catfish business is classified as large and promising, with an average income of Rp. 7,043,764.00/month. The average income is quite large compared to the income, it can be concluded that the catfish catfish business in Sidorahayu Village has good prospects in the future because it can be seen from the small production costs